Specialised information processing deficits and distinct metabolomics profiles following TM-domain disruption of Nrg1 - O'Tuathaigh, C.M.P.; Mathur, N.; O'Callaghan, M.J.; MacIntyre, L.; Harvey, R.; Lai, D.; Waddington, J.L.; Pickard, B.S.; Watson, D.G.; Moran, Paula M. (Oxford University Press, 2017)
While there is considerable genetic and pathologic evidence for an association between neuregulin 1 (NRG1) dysregulation and schizophrenia, the underlying molecular and cellular mechanisms remain unclear. Mutant mice containing disruption of the transmembrane (TM) domain of the NRG1 gene constitute a heuristic model for dysregulation of NRG1-ErbB4 signalling in schizophrenia. The present study focused on specialised behavioural and characterisation of hitherto un-characterised information processing phenotypes in this mutant line. Using a mass spectrometry-based metabolomics approach, we also quantified levels of unique metabolites in brain. Across two different sites and protocols, Nrg1 mutants demonstrated deficits in pre-pulse inhibition, a measure of sensorimotor gating that is disrupted in schizophrenia; these deficits were partially reversed by acute treatment with second-, but not first-, generation antipsychotic drugs. However, Nrg1 mutants did not show a specific deficit in latent inhibition, a measure of selective attention that is also disrupted in schizophrenia. In contrast, in the ‘what-where-when’ cognitive paradigm, Nrg1 mutants displayed sex-specific (males only) disruption of ‘what-when’ performance, indicative of impaired episodic memory. Differential metabolomic profiling revealed that these behavioural phenotypes were accompanied, most prominently, by alterations in lipid metabolism pathways. This study is the first to associate these novel physiological mechanisms, previously independently identified as being abnormal in schizophrenia, with disruption of NRG1 function. These data suggest novel mechanisms by which compromised neuregulin function from birth might lead to schizophrenia-relevant behavioural changes in adulthood.